Contents and Foreword of the SOSIOHUMANIKA Journal, Issue of November 2015 - SOSIOHUMANIKA, Editor Journal (ASPENSI in Bandung, Indonesia, 2015)
This journal, with ISSN 1979-0112, was firstly published on May 20, 2008 in the context to commemorate One Millenium of National Awakening Day in Indonesian. The SOSIOHUMANIKA journal is published twice a year i.e. every May and November. For period 2013 to 2018, the SOSIOHUMANIKA journal has been accredited by Ditjendikti Kemdikbud RI (Directorate-General of Higher Education, Ministry of Education and Culture of the Republic of Indonesia). Since issue of May 2014 to date, the SOSIOHUMANIKA journal has jointly been organized by the Lecturers of PPs UNIPA (Postgraduate Program, University of PGRI Adibuana) in Surabaya, East Java; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia.Â Surabaya, Indonesia: November 30, 2015.Â Dr. Haji Djoko Adi WalujoHonorable Patron of the SOSIOHUMANIKA Journal in Bandung, West Java; and Rector of UNIPA (University of PGRI Adibuana) in Surabaya, East Java, Indonesia.